Apolipoprotein E ε4 associates with microglial activation in early Braak regions independently of amyloid‐β and tau. (20th December 2022) - Ferrari‐Souza, João Pedro; Lussier, Firoza Z; Tissot, Cécile; Leffa, Douglas Teixeira; Ferreira, Pamela C.L.; Bellaver, Bruna; Brum, Wagner S.; Benedet, Andréa Lessa; Therriault, Joseph; Wang, Yi‐Ting; Chamoun, Mira; Servaes, Stijn; et al.
Abstract: Background: Recent evidence suggests that microglial activation sets the stage for tau spread in Alzheimer's disease (AD). However, the underpinnings of microglial activation in early regions of tau accumulation are poorly understood. The apolipoprotein E ( APOE ) ε4 allele is the strongest genetic risk factor for sporadic AD and influences microglial response in animal models of AD. Here, we tested the hypothesis that APOE ε4 carriership is associated with microglial activation in early Braak regions independently of amyloid‐β (Aβ) and tau pathologies. Method: We assessed 118 participants [79 cognitively unimpaired (CU), 23 with mild cognitive impairment (MCI), and 16 with AD dementia] with 50 years of age or older from the McGill TRIAD cohort. Individuals had available positron emission tomography (PET) for Aβ ([ 18 F]AZD4694), tau tangles ([ 18 F]MK6240), and microglial activation ([ 11 C]PBR28), as well as magnetic resonance imaging (MRI) and APOE genotyping. Braak I (transentorhinal) and Braak II (entorhinal and hippocampus) were defined as early regions of tau tangles accumulation. Result: Voxel‐wise analysis revealed that APOE ε4 carriership was associated with microglial activation mainly in regions corresponding to early Braak stages ( e.g ., transentorhinal, entorhinal, and hippocampus; Figure 1 ). In these regions, we observed that APOE ε4 carriership was associated with microglial activation independently of Aβ and tau pathologies (Braak I: β = 0.087, P < 0.001; Braak II: β = 0.053, P = 0.026; Table 1) . Furthermore, structural equation modeling demonstrated that microglial activation mediated the Aβ‐independent effect of APOE ε4 carriership on tau accumulation in regions corresponding to Braak I‐II (mediation effect size = 34.1%; Figure 2 ). Conclusion: Our results suggest a deleterious effect of APOE ε4 carriership on AD progression by contributing to microglial activation in regions of early tau accumulation (transentorhinal, entorhinal, and hippocampus). These findings can help to understand the influence of the APOE ε4 allele on AD pathogenesis, as well as provide insights for the development of drugs targeting the interplay between APOE ε4 and microglial activation.